Designing An Android Based Online Bus Ticket Booking Application In Sumatra - Ikhwan, Ali (International Conference on Sciences Development and Technology, 2022)
User Interface (UI) is a form of the graphical display directly related to the user. The user interface connects the user and the operating system to run the computer. This internet gave birth to many applications implemented in industry, education, government, and others. By utilizing the internet and building this application, we can reduce problems that occur in the manual system, such as queues and errors in data processing, and also facilitate technology users, especially online ticket booking applications. This internet gave birth to many applications implemented in industry, education, government, and others. By utilizing the internet and building this application, we can reduce problems that occur in the manual system, such as queues, and errors in data processing, and also facilitate users of technology, especially the use of online ticket booking application.